Interdisciplinary approach to cell–biomaterial interactions: biocompatibility and cell friendly characteristics of RKKP glass–ceramic coatings on titanium. (4th June 2015) - Ledda, Mario; De Bonis, Angela; Bertani, Francesca Romana; Cacciotti, Ilaria; Teghil, Roberto; Lolli, Maria Grazia; Ravaglioli, Antonio; Lisi, Antonella; Rau, Julietta V
Abstract: In this work, titanium (Ti) supports have been coated with glass–ceramic films for possible applications as biomedical implant materials in regenerative medicine. For the film preparation, a pulsed laser deposition (PLD) technique has been applied. The RKKP glass–ceramic material, used for coating deposition, was a sol–gel derived target of the following composition: Ca-19.4, P-4.6, Si-17.2, O-43.5, Na-1.7, Mg-1.3, F-7.2, K-0.2, La-0.8, Ta-4.1 (all in wt%). The prepared coatings were compact and uniform, characterised by a nanometric average surface roughness. The biocompatibility and cell-friendly properties of the RKKP glass–ceramic material have been tested. Cell metabolic activity and proliferation of human colon carcinoma CaCo-2 cells seeded on RKKP films showed the same exponential trend found in the control plastic substrates. By the phalloidin fluorescence analysis, no significant modifications in the actin distribution were revealed in cells grown on RKKP films. Moreover, in these cells a high mRNA expression of markers involved in protein synthesis, proliferation and differentiation, such as villin (VIL1), alkaline phosphatase (ALP1), β -actin ( β -ACT), Ki67 and RPL34, was recorded. In conclusion, the findings, for the first time, demonstrated that the RKKP glass–ceramic material allows the adhesion, growth and differentiation of the CaCo-2 cell line.